2021
DOI: 10.1186/s13046-021-02080-9
|View full text |Cite
|
Sign up to set email alerts
|

CIRP promotes the progression of non-small cell lung cancer through activation of Wnt/β-catenin signaling via CTNNB1

Abstract: Background Cold-inducible RNA binding protein (CIRP) is a newly discovered proto-oncogene. In this study, we investigated the role of CIRP in the progression of non-small cell lung cancer (NSCLC) using patient tissue samples, cultured cell lines and animal lung cancer models. Methods Tissue arrays, IHC and HE staining, immunoblotting, and qRT-PCR were used to detect the indicated gene expression; plasmid and siRNA transfections as well as viral inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…As a tumor suppressor, CIRBP decreases the proliferation in rectal carcinoma cells and ovarian cancer cells by binds the 5′ and 3′-UTRs of mRNAs, as well as poly U sequences at the 3′-ends to regulate the polyadenylation and 3′-end cleavage, and increases the translational efficiency of DNA damage response genes ATR, Trx-1, and RPA2 [ 28 ]. As a tumor promoter, CIRBP can promote proliferation and reduce apoptosis in breast cancer [ 29 ], prostate cancer [ 30 ], and lung carcinoma cells (A549) [ 31 ] by target mRNA. Importantly, data show that CIRBP induces ROS and mitochondrial DNA fragmentation and regulates macrophage autophagy through TLR4 signaling [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a tumor suppressor, CIRBP decreases the proliferation in rectal carcinoma cells and ovarian cancer cells by binds the 5′ and 3′-UTRs of mRNAs, as well as poly U sequences at the 3′-ends to regulate the polyadenylation and 3′-end cleavage, and increases the translational efficiency of DNA damage response genes ATR, Trx-1, and RPA2 [ 28 ]. As a tumor promoter, CIRBP can promote proliferation and reduce apoptosis in breast cancer [ 29 ], prostate cancer [ 30 ], and lung carcinoma cells (A549) [ 31 ] by target mRNA. Importantly, data show that CIRBP induces ROS and mitochondrial DNA fragmentation and regulates macrophage autophagy through TLR4 signaling [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its intracellular function as an RNA-binding protein to regulate gene expression [27][28][29], multiple studies have reported that CIRP can be secreted extracellularly and that eCIRP plays important roles in acute and chronic inflammatory diseases. A recent study showed that serum eCIRP levels were upregulated in patients with psoriasis [30], which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with TP53 and RB1 mutations have an increased risk of small cell lung cancer [34–36] . Mutations in PIK3CA and PTEN could activate the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (AKT) pathway, and the CTNNB1 mutation could affect the Wnt/β-catenin pathway and result in tumor proliferation and progression [37–40] . Amplification of CDK4 , CDK6 , and CCNE1 affects the transition of the G1/S cell cycle [41] .…”
Section: Egfr Concomitant Mutationsmentioning
confidence: 99%